杜威晚期四本社會哲學專書揭示的民主與教育要義 John Dewey’s Thoughts on Democracy and Education in His Four Later Works on Social Philosophy - 單文經 Wen-Jing Shan (臺灣教育社會學研究, 2017)
本研究就杜威所著《公眾及其問題：政治探究隨筆》、《新舊個人主義》、《自由主義與社會行動》及《自由與文化》，說明撰作緣起、解析內容、歸納旨趣，並揭示其民主與教育的要義。研究者有感於臺灣學者在探討杜威的民主與教育思想時，多以《學校與社會》、《兒童與課程》、《民主與教育》及《經驗與教育》等教育專著為切入點，而較少及於這四本專書，在探討其社會哲學思想時，則較少及於教育論著，乃撰寫本文，期能補苴罅漏、張皇幽眇。本研究於確認四本專書為杜威針對社會問題有感而發的專著 後，歸納出其等所呈顯的民主理論深化與概念釐清、社會制度重構與手段正用，以及民主目的與真教育的踐行等要義，並自現今的角度指出杜威較少注意種族、階級與性別等問題。 This article analyzes John Dewey’s thoughts on democracy and education, based on his four later works – The Public and Its Problems: An Essay in Political Inquiry, Individualism Old and New, Liberalism and Social Action, and Freedom and Culture. These works have received less attention than others such as School and Society, Child and Curriculum, Democracy and Education, and Experience and Education from local educationists investigating Dewey’s thoughts on democracy and education. This paper is intended to fill the gap. After confirming that these four works were conceived as Dewey’s special thoughts on social issues, three focal points were revealed – the deepening of his theory of democracy and clarification of related concepts, the reconstruction of social systems and the means by which this is to be achieved, and the purpose of democracy and the practice of genuine education. From a contemporary perspective, it is pointed out that little attention is paid to race, class and gender issues.